Multi-elemental composition of botanical preparations and probabilistic evaluation of toxic metals and metalloids intake upon dietary exposure - Varra, Maria Olga; Husáková, Lenka; Lanza, Giovanni Tommaso; Piroutková, Martina; Patočka, Jan; Ghidini, Sergio; Zanardi, Emanuela (Elsevier Science, 2024)
The aim of this study was to evaluate the inorganic elemental composition (49 elements) of 29 botanical preparations obtained from fruits, leaves, peels, seeds, roots, fungi, and spirulina by using inductively coupledmass spectrometry and a mercury analyzer. Simultaneously, the risk associated with the chronic dietary exposure to 12 toxic metals and metalloids among the European population was evaluated by using a probabilistic approach based on Monte Carlo simulations. The analysis revealed worrying intake levels of Al, As, and Ni, primarily stemming from the consumption of spirulina-, peel-, and leaf-based botanicals by younger age groups. The intake of As from all analyzed botanicals posed a significant risk for infants, yielding margins of exposure (MOEs) below 1, while those deriving from peel-based botanicals raised concerns across all age groups (MOEs = 0.04-2.3). The consumption of peel-based botanicals contributed substantially (13-130%) also to the tolerable daily intake of Ni for infants, toddlers, and children, while that of spirulina-based botanicals raised concerns related to Al intake also among adults, contributing to 11-176% of the tolerable weekly intake of this element. The findings achieved underscore the importance of implementing a monitoring framework to address chemical contamination of botanicals, thus ensuring their safety for regular consumers.
Multiprvková analýza rostlinných přípravků a statistické hodnocení rizika příjmu s nimi spojených toxických kovů a metaloidů
Keywords: Food safety; Food supplements; Heavy metals; Monte Carlo simulations; Risk assessment; Multiprvková; analýza; Potravinové doplňky; Těžké kovy; Monte Carlo simulace; Hodnocení rizika